(untitled) (Bridging Cultures, 2018)
Artificial intelligence (AI) is defined as “the scientific study and engineering of intelligent machines” (Luxton, 2013). This technology allows devices and tools to behave in a human-like intelligent manner to “emulate reasoning and language processing” (2013). According to a Report to ARPA on Twenty-First Century Intelligent (n.d.), AI has emerged to answer researchers’ argument that computer systems are “rigid, complex, and incapable of rapid change”. By becoming “intelligent”, these systems can adapt to the fast-evolving technology and meet technological needs of major national areas in communication, military, healthcare, and education. As a result, in the past two decades, we have witnessed major advancements in the emerging and development of smart devices such as the smartphone. In fact, the Report to ARPA indicates that researchers already predicted a future in which people would have a single device integrated with telephone, Internet, television capabilities, news, and, electronic mail.